Alternative Substitutional Box Structures for DES - Ozkaynak, Fatih; Muhamad, Mukhlis I. (Ieee, 2018)
The DES algorithm is an important encryption protocol that has influenced many cryptology studies. It is still used today in many practical applications such as electronic passport. But it is an important problem that the design parameters of substitution boxes of this algorithm are unknown. In this work, we have proposed alternatives to DES s-box structures to solve this problem. The analysis results of the proposed structures are equivalent to DES s-box structures.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: block cipher; DES; substitution box; chaos